Exploring Digital Storytelling Techniques Inspired by Natyashastra: Bridging Tradition and Innovation - Sahoo, Somanath (Bodhi: An Interdisciplinary Journal, 2025)
This article approaches the convergence of ancient Bharatavarshiya aesthetic principles as described in the Natyashastra with contemporary digital storytelling tools. It aims to explore the ways in which the enduring wisdom of Natyashastra might enhance and enliven digital narrative encounters. The study commences by clarifying the fundamental ideas of the Natyashastra, an ancient Sanskrit treatise on performing arts ascribed to the sage Bharat Muni. It also investigates how digital storytelling platforms utilize approaches inspired by Natyashastra to effectively connect and fascinate people in the digital age. Using examples from animation, gaming, interactive storytelling apps, and immersive experiences, the study analyzes the modifications and reinterpretations of narrative structure, character development, and emotional resonance for digital platforms. Moreover, the possible connections between Natyashastra and cutting-edge technologies like virtual reality (VR), augmented reality (AR), and mixed reality (MR), which provide novel opportunities for engaging storytellingencounters also have been explored. It is also aimed to discover overarching principles and best practices that bridge the gap between tradition and innovation in storytelling by conducting a comparative examination of traditional Natyashastra techniques and their digital successors. In addition, the study examines the ethical implications of using cultural heritage for digital storytelling, specifically focusing on concerns related to cultural authenticity, representation, and ownership in the digital domain.